The Theological Sources of the Torah and Labor (Torah U'melakha) Yeshivas - Mashiaḥ, Amir (Religions, 2023)
In this article, I seek to reveal the theological sources of the Israeli high school yeshivas designated “Torah U’melakha” (Torah and labor). High school yeshivas are schools for 9th–12th grade boys that offer religious studies in the first half of the day and secular studies, i.e., science and languages, in the second half. These schools serve mainly religious Zionist and modern orthodox society. Torah U’melakha yeshivas are high school yeshivas that are unique for combining vocational studies in the curriculum, such that graduates acquire a trade and can serve in the army and join the labor force in their field of expertise. Over the years, some of the Torah U’melakha yeshivas were subsequently closed and others changed their nature from vocational to technological. However, the educational trend toward “Torah and labor” has not disappeared. Vocational education, which became technological as well, has been assimilated in nearly all high school yeshivas, which, to a great degree, made the Torah U’melakha yeshivas redundant. The ideological and theological value of engaging in “Torah and work” became embedded in the pedagogic consciousness of religious Zionism and is continuing to infuse the many high school yeshivas in Israel and elsewhere.